Tunable nanoblock lasers and stretching sensors. Issue 37 (12th September 2016) - Lu, T. W.; Wang, C.; Hsiao, C. F.; Lee, P. T.
Abstract : We propose and demonstrate a reconfigurable, reliable, and tunable 1D nanoblock laser with large wavelength tunability, wide wavelength tuning range, and high sensitivity for stretching sensing. Abstract : Reconfigurable, reliable, and robust nanolasers with wavelengths tunable in the telecommunication bands are currently being sought after for use as flexible light sources in photonic integrated circuits. Here, we propose and demonstrate tunable nanolasers based on 1D nanoblocks embedded within stretchable polydimethylsiloxane. Our lasers show a large wavelength tunability of 7.65 nm per 1% elongation. Moreover, this tunability is reconfigurable and reliable under repeated stretching/relaxation tests. By applying excessive stretching, wide wavelength tuning over a range of 80 nm (spanning the S, C, and L telecommunication bands) is successfully demonstrated. Furthermore, as a stretching sensor, an enhanced wavelength response to elongation of 9.9 nm per % is obtained via the signal differential from two nanoblock lasers positioned perpendicular to each other. The minimum detectable elongation is as small as 0.056%. Nanoblock lasers can function as reliable tunable light sources in telecommunications and highly sensitive on-chip structural deformation sensors.